IMPLEMENTASI STRATEGI BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO ROTI - Lashwaty, Nina Dewi (Sekolah Tinggi Ilmu Ekonomi Semarang, 2025)
The study was carried out in a quantitative descriptive method. The independent variable consists of 7 aspects of the marketing mix. The dependent variable is the purchasing decision. A Cronbach's Alpha of 0.961 reflects that the questionnaire is reliable. Based on the results of the one-stage Multiple Linear Regression Analysis, it was found that the product, price, promotion, process, physical evidence have positive sign which means it is associated in the same direction with purchasing decisions. Aspects of place and people can be interpreted as having an inverse association with purchasing decisions. From the results of the Simultaneous Test, it was found the simultaneous impact of 7 aspects of the marketing mix on purchasing decisions. The Individual Test indicates that promotion, physical evidence, product, process have an individual impact on purchasing decisions. On the other hand, price, place, people are aspects that do not have an individual impact, in fact place and people have an inverse association with purchasing decisions. Promotion has the most significant impact on purchasing decisions. An R square of 0.920 means that 92% of purchasing decisions are as a result of managing the 7P marketing mix aspects which are well managed by Mungil Bakery Shop Sukoharjo.